Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1099/jmm.0.008094-0
|View full text |Cite
|
Sign up to set email alerts
|

Reduced susceptibility to carbapenems in Klebsiella pneumoniae clinical isolates associated with plasmid-mediated β-lactamase production and OmpK36 porin deficiency

Abstract: Two carbapenem-non-susceptible Klebsiella pneumoniae isolates, Z2554 and Z2110, were collected from a hospital in China and analysed by PFGE. K. pneumoniae Z2554 and Z2110 were genetically unrelated and showed resistance to ertapenem, and reduced susceptibility to imipenem and meropenem. Analysis of their b-lactamases indicated that K. pneumoniae Z2554 produced TEM-1 and CTX-M-14 b-lactamases, whilst Z2110 produced a plasmid-mediated AmpC b-lactamase, DHA-1, in addition to TEM-1 and CTX-M-14. SDS-PAGE analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
43
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 33 publications
5
43
1
Order By: Relevance
“…Strains deficient in both OmpK35 and OmpK36 and containing carbapenem-hydrolyzing ␤-lactamase are obviously resistant to ertapenem (54). However, in 2009, clinical ertapenem-resistant strains lacking OmpK36 but not OmpK35 were reported in China (55). This is surprising, because OmpK35 should be able to allow an influx of this compound (MW, 475), although OmpK36 may also make significant contribution in view of its not-so-large size.…”
Section: Discussionmentioning
confidence: 67%
“…Strains deficient in both OmpK35 and OmpK36 and containing carbapenem-hydrolyzing ␤-lactamase are obviously resistant to ertapenem (54). However, in 2009, clinical ertapenem-resistant strains lacking OmpK36 but not OmpK35 were reported in China (55). This is surprising, because OmpK35 should be able to allow an influx of this compound (MW, 475), although OmpK36 may also make significant contribution in view of its not-so-large size.…”
Section: Discussionmentioning
confidence: 67%
“…The majority of resistant Klebsiella isolates exhibit both expression of an extendedspectrum beta-lactamase (ESBL) and halted expression of at least one outer membrane porin (4,5). Porin loss has been clearly shown to enhance levels of antibiotic resistance, and ESBL-positive K. pneumoniae isolates commonly exhibit loss of OmpK35 and OmpK36, which both function in nonspecific transport across the outer membrane (6)(7)(8).…”
mentioning
confidence: 99%
“…A clustering analysis based on average nucleotide identity (ANI) (6) revealed that strain DSM 30104 T was most closely related to K. pneumoniae KCTC 2242 (99.03% ANI). Lower ANI values (approximately 98.75% to 98.99%) were found in comparisons to other K. pneumoniae strains sequenced so far (5,7,9,11,13,14). The KCTC 2242 strain was previously reported to produce 2,3-butanediol and to be used in industrial applications as a potential valuable fuel additive (11).…”
mentioning
confidence: 97%
“…The (5,7,9,11,13,14). A clustering analysis based on average nucleotide identity (ANI) (6) revealed that strain DSM 30104 T was most closely related to K. pneumoniae KCTC 2242 (99.03% ANI).…”
mentioning
confidence: 99%